2006
DOI: 10.1002/aheh.200500631
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macrofauna in Tunca River (Turkey) and their relationships with environmental variables

Abstract: The numerical and proportional distributions of benthic macroinvertebrates in Tunca (Tundja, Tundzha) River (Edirne/Turkey) were determined from July 2002 to June 2003 at monthly intervals at four different stations. It was found that the benthic macrofauna consisted of 63% Oligochaeta, 24% Chironomidae larvae, and 13% Varia by numbers. According to the Shannon-Wiener index, Tunca River had a diversity of 1.36; station 2 and September were found to have the highest diversity while station 4 and December to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Also, the data on aquatic and semi-aquatic Oligochaeta from the previous printed studies which have been performed at Lake Terkos by Çamur-Elipek (2003) and at Tunca River by Kırgız et al (2005), Çamur-Elipek et al (2006) were discussed in the present study.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Also, the data on aquatic and semi-aquatic Oligochaeta from the previous printed studies which have been performed at Lake Terkos by Çamur-Elipek (2003) and at Tunca River by Kırgız et al (2005), Çamur-Elipek et al (2006) were discussed in the present study.…”
Section: Methodsmentioning
confidence: 74%
“…Tunca River (Kırgız et al, 2005;Çamur-Elipek et al, 2006) Lake Terkos (Çamur-Elipek, 2003) In the present study The Oligochaeta samples were identified to the possible lowest taxonomic level under stereobinocular microscope by using the literatures of Brinkhurst (1971Brinkhurst ( , 1978, Brinkhurst and Jamieson (1971), Brinkhurst and Wetzel (1984), Brinkhurst (1998), Milligan (1997), Sperber (1948Sperber ( , 1950, Timm (1999), Wetzel et al (2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These four species are reported to be tolerant of severe pollution and have been found in a stream degraded by industrial effluents (Maciorowski et al 1977;Harman 1979). Stylaria lacustris, Nais elinguis, Pristina jenkinae and Aulophorus furcatus were reported to occur in abundance in stony bottomed, muddy substratum, organically enriched streams and lakes in Turkey (Çamur-Elipek et al 2006;Arslan and Şahin 2006;Akbulut et al 2009). This fact can be explained by the euryoeic character of four naidine species, as reported by Pascar-Gluzman and Dimentman (1984) and Davis (1982).…”
Section: Discussionmentioning
confidence: 99%
“…Oligochaeta, a subclass of the Clitellata, are broadly distributed worldwide and frequently are the most abundant in many freshwater ecosystems and they are widely used for monitoring river and lake pollution. Despite, studies about freshwater oligochaeta have increased in recent years such as, [1], [2], [3], [4], [5], [6] regarding our knowledge of the freshwater oligochaeta fauna of Turkey, large areas still remain under-or even unexplored. Up to now, only 107 species (5 of them endemic) have been reported from different parts of Turkey.…”
Section: Introductionmentioning
confidence: 99%